Desain Mockup Sistem Informasi Simpanan Pelajar (SIMPEL) dengan Pendekatan User-Centered Design - muhamad syarif (Jurnal Sistem Informasi Akuntansi, 2025)
Simpanan Pelajar (SIMPEL) program is designed to cultivate a saving habit among students from an early age. However, many schools still manage student savings manually, which is prone to data loss, recording errors, and lack of transparency for students and parents. This research aims to design a mockup for a web-based SIMPEL information system using the User-Centered Design (UCD) approach, ensuring the system aligns with user needs particularly students, parents, and school treasurers. The study adopts the ISO 9241-210:2010 UCD framework, involving stages such as user requirement analysis, low fidelity wireframe design, high-fidelity mockup development, usability feedback, and refinement. Data collection methods include questionnaires and interviews with stakeholders. The results revealed that users required real-time transaction records, transparent access, and a simple interface. The final mockup design features customized dashboards for each user role and supports efficient savings management. Usability testing yielded a score of 87.5%, indicating a very good level of usability and confirming that the interface is intuitive and aligned with user expectations. This study contributes to the development of digital financial literacy tools in educational environments and highlights the effectiveness of UCD in producing user-friendly financial systems for schools.